Correlation of Fine Needle Aspiration Cytology with Histopathology in the Diagnosis of Solitary Thyroid Nodule. (18th April 2010) - Gupta, Manoj; Gupta, Savita; Gupta, Ved Bhushan
Abstract : Background . Fine needle aspiration cytology is considered the gold standard diagnostic test for the diagnosis of thyroid nodules. Fine needle aspiration cytology is a cost effective procedure that provides specific diagnosis rapidly with minimal complications. Based on the cytology findings, patients can be followed in cases of benign diagnosis and subjected to surgery in cases of malignant diagnosis thereby decreasing the rate of unnecessary surgery. Purpose of the present study was to correlate the fine needle aspiration cytology findings with histopathology of excised specimens. Material and Methods . This was a prospective study conducted on 75 consecutive patients between January 2003 and December 2005. All patients with clinically diagnosed solitary thyroid nodule who were clinically and biochemically euthyroid were included for study. Patients with multinodular goitre and who were hypothyroid or hyperthyroid were excluded from the study. Results . The sensitivity, specificity, accuracy, false positive rate, false negative rate, positive predictive value, and negative predictive value of FNAC for the diagnosis of neoplastic solitary thyroid nodules were 80%, 86.6%, 13.3%, 20%, 80%, and 86.6%, respectively. Commonest malignancy detected was papillary carcinoma in 12 patients. Conclusions . Fine needle aspiration cytology is a simple, easy to perform, cost effective, and easily repeated procedure for the diagnosis of thyroid cancer. It is recommended as the first line investigation for the diagnosis of solitary thyroid nodule.